Systemic vulnerability of coastal territories to erosion and marine flooding: A conceptual and methodological approach applied to Brittany (France). (August 2022) - Le Berre, Iwan; Meur-Ferec, Catherine; Cuq, Véronique; Guillou, Elisabeth; Lami, Thibaud; Le Dantec, Nicolas; Letortu, Pauline; Lummert, Caroline; Philippe, Manuelle; Rouan, Mathias; Noûs, Camille; Hénaff, Alain
Abstract: The attractiveness of the coasts tends to increase their exposure to erosion and marine flooding risks. This exposure is exacerbated by the effects of climate change, in particular sea level rise. To contribute to strategic thinking on the vulnerability of coastal areas, it is essential to develop, share and collectively maintain relevant knowledge on risks. This article will present the thinking behind the setting up of a coastal risks observatory in Brittany, a region located in north-western France. It relies on a conceptual approach to systemic vulnerability based on four components: hazards, assets, management, and social representations. Hazards and assets underpin the notion of risk and tend to increase the vulnerability, management tends to mitigate it, and representations can play a part in increasing or decreasing it depending on the context. To understand and analyse this system of vulnerability, our approach is based on the generation of a set of 62 indicators combined into different types of indices. A web-GIS interface was developed to navigate through and map this system of vulnerability. The difficulties associated with this type of synthetic approach will be discussed, whether they are related to data availability, to the links between scientific research and operational territorial management requirements, or to an understanding of the dynamics of all of the vulnerability components and their interactions. Ultimately, the approach developed has been successful in mobilising scientific and operational stakeholders around the co-construction of a diagnosis of territories with regard to their vulnerability to coastal risks. Graphical abstract: Image 1 Highlights: Demographic and environmental trends increase the exposure of coastal areas to risks. Systemic vulnerability relies on hazards, assets, management and social representations. This complex system is analysed through 62 indicators combined into several indices. A web-GIS interface allows to navigate through this system of vulnerability. It helps scientific and stakeholders to share a common diagnosis on coastal risks.